1991
DOI: 10.21273/hortsci.26.4.368
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Effects of Alfalfa Plant Residues on Emergence and Growth of Cucumber Seedlings

Abstract: Growth chamber tests demonstrated that alfalfa (Medicago sativa L.) residue is toxic to cucumber (Cucumis sativus L.) seed germination and seedling growth. Ground alfalfa roots at 0.5% (w/w, dry weight) inhibited germination when added to the growing medium. Alfalfa roots at 0.5% were also toxic to pregerminated cucumber seed. However, cucumber seedlings grew normally if this same medium was watered and incubated for >1 day before planting. Alfal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 5 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…The high cover and phytomass of lucerne in the first years caused weed suppression by increased shading of the soil surface (Güsewell & Edwards 1999), and/or the competitive exclusion of short‐lived weeds (Bischoff, Auge & Mahn 2005). An allelopathic effect of lucerne may be responsible for low weed cover: Ells & McSay (1991) showed that lucerne leaf extract (containing phenolic allelochemicals) was detrimental to germination and differentiation of susceptible plants.…”
Section: Discussionmentioning
confidence: 99%
“…The high cover and phytomass of lucerne in the first years caused weed suppression by increased shading of the soil surface (Güsewell & Edwards 1999), and/or the competitive exclusion of short‐lived weeds (Bischoff, Auge & Mahn 2005). An allelopathic effect of lucerne may be responsible for low weed cover: Ells & McSay (1991) showed that lucerne leaf extract (containing phenolic allelochemicals) was detrimental to germination and differentiation of susceptible plants.…”
Section: Discussionmentioning
confidence: 99%
“…Lettuce (Lactuca sativa L.), tomato (Solanum lycopersicum L.), carrot (Daucus carota L.), and cucumber (Cucumis sativus L.) are the most commonly used species for the bioassays (Ells & McSay 1991;Macıìas et al 1999;Xuan et al 2004;Arowosegbe & Afolayan 2012), as they are sensitive plants to phytotoxins and germinate uniformly. Vyvyan (2002) suggested that barnyardgrass is suitable for the study of allelopathy in rice but both monoand dicotyledonous plants should be used in bioassays to assess the potential selectivity of the agents.…”
Section: Allelopathic Effect Of Methanol Extracts From Tinospora Tubementioning
confidence: 99%
“…Allelopathic effects of alfalfa plant residues on emergence and growth of seedlings have been reported. Alfalfa extracts inhibited seed germination in cotton (Megie et al, 1967), corn (Guenzi et al, 1964), and cucumber (Ells and McSay, 1991). Biological activity possibly could contribute to poor germination in the unincubated medium.…”
Section: Resultsmentioning
confidence: 98%
“…Incubation also will prevent allelopathic interactions between amendment and the germinating seedlings. Allelopathic effects of alfalfa plant residue on seed germination and growth of cucumber seedlings have been reported (Ells and McSay, 1991). Selection of a particular kind and rate of organic amendment should be made based on cost-effectiveness and effects on medium pH and EC, seed germination, plant height, stem diameter, chlorophyll content, plant biomass, and sustainability of the product.…”
Section: Resultsmentioning
confidence: 99%